Faktor-Faktor Yang Mempengaruhi Kesuksesan E-Commerce UKM Kain Tradisional Palembang - Irma - Salamah (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2018)
This study empirically examines the factors that influence the success of e-commerce in traditional cloth of Palembang SMEs using the DeLone & McLean approach. The variables used are system quality, service quality, information quality, and use. The problem in this study is, there are still many SMEs in the traditional cloth of Palembang that have not used e-commerce technology in their business processes, so it is necessary to investigate what factors influence the use of e-commerce technology in the traditional cloth of Palembang SMEs. The samples taken are 35 traditional Palembang cloth SMEs that have used e-commerce in their business processes. This research was conducted with exploratory and empirical studies. In the exploratory study conducted by identifying the success factors of SI e-commerce based on the DeLone & McLean model. Next, make a hypothesis between the success factors of IS. An empirical study was conducted to verify the hypothesis that was made. Based on these two studies and using the path analysis method, an e-commerce model will be obtained for the traditional cloth Palembang SMEs. The results obtained are system quality variables that do not directly affect the use of use of e-commerce, service quality directly affects use of e-commerce, and information quality directly affects use of e-commerce.